2011
DOI: 10.1002/cncr.25945
|View full text |Cite
|
Sign up to set email alerts
|

Boswellia serrata acts on cerebral edema in patients irradiated for brain tumors

Abstract: BACKGROUND:Patients irradiated for brain tumors often suffer from cerebral edema and are usually treated with dexamethasone, which has various side effects. To investigate the activity of Boswellia serrata (BS) in radiotherapyrelated edema, we conducted a prospective, randomized, placebo-controlled, double-blind, pilot trial. METHODS: Forty-four patients with primary or secondary malignant cerebral tumors were randomly assigned to radiotherapy plus either BS 4200 mg/day or placebo. The volume of cerebral edema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…In addition, frankincense is considered as an alternative medicine in Arab countries and has been used as an anti-cancer agent to treat neoplastic diseases. In a prospective, randomized, placebo-controlled, double-blind clinical trial conducted in patients irradiated for brain tumors, an extract prepared from Boswellia serrata gum resins (H15) significantly reduces cerebral edema with anti-tumor properties, without severe adverse effects [9]. Boswellia serrata extracts is included as an adjuvant agent in patients with high grade gliomas under an ongoing phase II clinical trial ( http://www.cancer.gov/clinicaltrials/search/view?cdrid=445603&version=healthprofessional).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, frankincense is considered as an alternative medicine in Arab countries and has been used as an anti-cancer agent to treat neoplastic diseases. In a prospective, randomized, placebo-controlled, double-blind clinical trial conducted in patients irradiated for brain tumors, an extract prepared from Boswellia serrata gum resins (H15) significantly reduces cerebral edema with anti-tumor properties, without severe adverse effects [9]. Boswellia serrata extracts is included as an adjuvant agent in patients with high grade gliomas under an ongoing phase II clinical trial ( http://www.cancer.gov/clinicaltrials/search/view?cdrid=445603&version=healthprofessional).…”
Section: Discussionmentioning
confidence: 99%
“…A methanol extract of Boswellia serrata inhibits abnormal skin cell proliferation induced by 12-O-tetradecanoylphorbol-13-acetate (TPA) and tumor promotion initiated by 7,12-dimethylbenz[a]anthracene (DMBA) in a mouse model [8]. In a human clinical study, a Boswellia serrata resin extract has been shown to reduce cerebral edema and potential anti-cancer activity in patients irradiated for brain tumors [9]. These studies suggest that gum resins of Boswellia species contain active ingredients that have anti-cancer activity.…”
Section: Introductionmentioning
confidence: 99%
“…They have been studied or used for a variety of diseases including cancer, analgesia, asthma inflammation, arthritis, and colitis [6]. Clinically, B. serrata resin extracts can significantly reduce cerebral edema in patients [7], showing promise as a new agent for cardiovascular diseases. Furthermore, the European Medicines Agency granted extracts of B. serrata gum resin as the orphan drug to treat brain edema [8].…”
Section: Introductionmentioning
confidence: 99%
“…A reduction of cerebral edema of >75% was found in 60% of patients receiving BS and in 26% of patients receiving placebo (P ¼ .023) compared with baseline and if measured immediately after the end of radiotherapy and BS/placebo treatment. These findings may be based on an additional anti-tumor effect and BS significantly reduced cerebral edema measured by MRI in the study population and it could potentially be steroid-sparing for patients receiving brain irradiation 55 .…”
Section: Anti-arthritic Activitymentioning
confidence: 88%